Applying e-commerce in business - Tassabehji, Rana (Sage, 2003)
Applying e-commerce in Business provides an understanding of e-commerce by deconstructing it into its main constituents and explaining how they fit together. The objective is to introduce some consistency to the often-contradictory views about e-commerce, bringing together different academic and management theories and frameworks into a coherent whole.